1997
DOI: 10.1007/s004420050202
|View full text |Cite
|
Sign up to set email alerts
|

Invasive capacity of Tamarix ramosissima in a Mojave Desert floodplain: the role of drought

Abstract: Tamarix ramosissima (Tamaricaceae) is a woody phreatophyte that has invaded thousands of hectares of floodplain habitat in the southwestern U.S. In this study, we examined the response of gas exchange and stem sap flow of Tamarix and three co-occurring native phreatophytes (Pluchea sericea (Asteraceae), Prosopis pubescens (Fabaceae) and Salix exigua (Salicaceae)) to drought conditions in an early successional floodplain community in the Mojave Desert of southern Nevada. In an analysis of a size/age series of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
141
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(145 citation statements)
references
References 27 publications
2
141
1
1
Order By: Relevance
“…No irrigation effect was found on its Pn, gs, Tr, c pre , c mid of uncovering some physiological bases in relation to its phreatophytic nature (Cleverly et al 1997;Xu & Li 2006). Compared with the 20-year-old T. ramosissima, the threeyear-old T. ramosissima depended heavily on soil water in the middle profile (80Á140 cm), implying the age effect on water use strategy of this species.…”
Section: Discussionmentioning
confidence: 87%
“…No irrigation effect was found on its Pn, gs, Tr, c pre , c mid of uncovering some physiological bases in relation to its phreatophytic nature (Cleverly et al 1997;Xu & Li 2006). Compared with the 20-year-old T. ramosissima, the threeyear-old T. ramosissima depended heavily on soil water in the middle profile (80Á140 cm), implying the age effect on water use strategy of this species.…”
Section: Discussionmentioning
confidence: 87%
“…Local reductions in the groundwater level may be caused by species that effectively exploit groundwater. Saltcedar can reach a lower water table and use more water per unit sapwood than several native species (Sala et al 1996;Cleverly et al 1997;Horton & Clark 2001). Shafroth et al (2000) found that saltcedar saplings were significantly less vulnerable than indigenous species to groundwater depletion.…”
Section: Phil Trans R Soc Lond B (2002)mentioning
confidence: 99%
“…Shafroth et al (2000) found that saltcedar saplings were significantly less vulnerable than indigenous species to groundwater depletion. This competitive advantage could lead to increased establishment of saltcedar, lowering the water table further and causing the loss of more native trees (Cleverly et al 1997). Saltcedar is also salt tolerant and excretes salts that may reduce the germination of salt-sensitive species (Busch & Smith 1995).…”
Section: Phil Trans R Soc Lond B (2002)mentioning
confidence: 99%
“…Following decreasing reproduction and increasing mortality of native trees, drought-tolerant species such as saltcedar (Tamarisk spp.) and Russian olive (Elaeagnus angustifolia) may be released from competition, increasing their invasive capacity (Cleverly et al, 1997;Katz and Shafroth, 2003). A combination of increased frequency of heavy rains and decreased magnitude of spring floods, predicted by other climate change studies, may benefit late-successional species such as Arizona Walnut (Juglans major), mesquites (Prosopis spp.…”
Section: Potential Response To Future Changesmentioning
confidence: 99%